2020
DOI: 10.1186/s12933-020-00998-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial 8-hydroxy-2′-deoxyguanosine and coronary artery disease in patients with type 2 diabetes mellitus

Abstract: Background: Little is known about whether mitochondria 8-hydroxy-2′-deoxyguanosine (8-OHdG), a biomarker of mitochondrial DNA (mtDNA) oxidative damage, contributes to the development of coronary artery disease (CAD) in diabetic patients. Here, we explored the associations of mtDNA 8-OHdG in leukocytes with obstructive CAD, coronary stenosis severity, cardiovascular biomarkers, and 1-year adverse outcomes after coronary revascularization in patients with type 2 diabetes mellitus (T2DM). Methods: In a total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…All alphabetical cross references in this figure ( a, b, c … ) are linked to literature reference numbers in the figure legend. The respective references are as follows: a [ 75 ], b [ 83 ], c [ 124 ], d [ 184 ], e [ 85 ], f [ 96 ], g [ 125 ], h [ 88 ], i [ 120 ], j [ 77 ], k [ 86 ], l [ 98 ], m [ 126 ], n [ 185 ], o [ 87 ], p [ 89 ], q [ 90 ], r [ 108 ], s [ 110 ], t [ 111 ], u [ 114 ], v [ 140 ], w [ 141 ], x [ 145 , [148] , [149] , [150] , [151] , [152] ], y [ 160 ], z [ [239] , [240] , [241] ], & [ 187 ]. Open access source for body image can be found at Pixabay ( https://pixabay.com/de/photos/anatomie-frau-mensch-k%C3%B6rper-haut-254120/ ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All alphabetical cross references in this figure ( a, b, c … ) are linked to literature reference numbers in the figure legend. The respective references are as follows: a [ 75 ], b [ 83 ], c [ 124 ], d [ 184 ], e [ 85 ], f [ 96 ], g [ 125 ], h [ 88 ], i [ 120 ], j [ 77 ], k [ 86 ], l [ 98 ], m [ 126 ], n [ 185 ], o [ 87 ], p [ 89 ], q [ 90 ], r [ 108 ], s [ 110 ], t [ 111 ], u [ 114 ], v [ 140 ], w [ 141 ], x [ 145 , [148] , [149] , [150] , [151] , [152] ], y [ 160 ], z [ [239] , [240] , [241] ], & [ 187 ]. Open access source for body image can be found at Pixabay ( https://pixabay.com/de/photos/anatomie-frau-mensch-k%C3%B6rper-haut-254120/ ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Prognostic value of classical oxidative stress markers for cardiovascular risk. ( A ) Association of markers of lipid peroxidation (isoprostane [8-iso-PGF2α] and malondialdehyde [MDA]) [ 75 , 83 , 85 ], nitro-oxidative stress (3-nitrotyrosine [3-NT]) [ 96 ], oxidative mitochondrial DNA damage (8-hydroxy-deoxyguanosine [8-OHdG]) [ 120 ] and derivatives of reactive oxygen metabolites (d-ROMs) [ 125 ] with cardiovascular risk in the comparison of healthy subjects with cardiovascular disease patients. ( B ) Associations of d-ROM levels and total thiol levels (TTL) with cardiovascular disease-specific mortality (adjusted for age and sex).…”
Section: Classical “Oxidative Stress” Biomarkers In Human Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…T2DM patients with CAD were classified into one-, two-, or three-vessel disease according to the number of diseased coronary arteries. The luminal diameter narrowing of left main coronary artery ≥ 50% was considered as three-vessel disease [ 17 ]. According to the method described in the literature [ 18 ], the Gensini score was calculated to assess the severity of CAD by two independent experienced cardiologists who were blinded to the clinical and procedural data.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of MMP2 and MMP9 were increased in ST-segment elevation myocardial infarction, non-ST segment elevation myocardial infarction and unstable angina pectoris (UA) compared to the control group (P < 0.05) [140] . Also, Wang and colleagues showed that increased mtDNA 8-OHdG could increase the odds of having coronary artery disease (CAD) (OR = 1.38), coronary stenosis (OR = 1.29), and higher levels of C-reactive protein [141] . Although these findings supported the notion that mitochondrial dysfunction could contribute to the development of CVD, the exact mechanism for that association is still unknown.…”
Section: Mitochondria and Cardiovascular Diseasesmentioning
confidence: 99%